Corporate social responsibility and employee performance in China’s manufacturing sector: Exploring the roles of altruistic values and organizational identification - Kaixian Fu; Jirapong Ruanggoon; Jakkrit Thavorn (PLoS ONE, 2026)
Background Few studies exploring the relationship between corporate social responsibility(CSR)and employee performance through Social Identity Theory (SIT) have specifically examined the boundary condition of altruistic values within China’s authoritarian cultural context. Objectives This study aims to examine the mechanism of CSR’s effect on employee performance in an authoritarian cultural setting, thereby advancing SIT and informing the enhancement of organizational management practices in China. Methods Using a combination of purposive and convenience sampling, a survey was administered to 432 employees from seven manufacturing firms in Sichuan Province in October 2024. All constructs, including perceived CSR, employee performance, organizational identification, and altruistic values, were assessed on 5-point Likert scales. Pearson correlation and linear regression analyses were then conducted to examine the hypothesized relationships. Results Descriptive statistics revealed that the manufacturing employees exhibited high perceived CSR, strong organizational identification, moderate in-role performance, high extra-role performance, and low altruistic values. Moreover, regression analysis confirmed that perceived CSR has strong effects on both in-role ( β = 0.44, p < 0.01) and extra-role performance ( β = 0.40, p < 0.01), and organizational identification ( β = 0.39, p < 0.01). Organizational identification mediated for approximately 20% of the relationship between perceived CSR and both in-role and extra-role performance, and altruistic values served as a significant negative moderator ( β = −0.10, p < 0.05) between perceived CSR and organizational identification. Conclusions SIT partially explains the effect of CSR on employee performance among Chinese manufacturing employees, revealing organizational identification as a mediator moderated by altruistic values. This insight offers Chinese managers a basis to enhance employee performance in the CSR initiatives process.